1999
DOI: 10.1007/pl00013819
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression of a cDNA encoding copper/zinc superoxide dismutase from cultured cells of cassava (Manihot esculenta Crantz)

Abstract: A cDNA, mSOD1, encoding cytosolic copper/ zinc superoxide dismutase (CuZnSOD) was cloned and characterized from cell cultures of cassava (Manihot esculenta Crantz) which produce a high yield of SOD. mSOD1 encodes a 152-amino acid polypeptide with a pI value of 5.84. Southern analysis using an mSOD1-speci®c probe indicated that a single copy of the mSOD1 gene is present in the cassava genome. The mSOD1 gene is highly expressed in cultured cells, as well as in intact stems and tuberous roots. It is expressed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
16
2
1
Order By: Relevance
“…Guan and Scandalios (1998) reported that one of two highly conserved Cu/Zn-SOD genes in Zea mays was regulated by ABA. While Lee et al (1999) showed that the cytosolic Cu/Zn-SOD gene of cassava was induced by wounding stress and application of MJ, which is a known mediator of wounding stress. These findings imply that expression of the cytosolic Cu/Zn-SOD gene is regulated in a species-specific manner.…”
Section: Northern Blot Analysesmentioning
confidence: 98%
“…Guan and Scandalios (1998) reported that one of two highly conserved Cu/Zn-SOD genes in Zea mays was regulated by ABA. While Lee et al (1999) showed that the cytosolic Cu/Zn-SOD gene of cassava was induced by wounding stress and application of MJ, which is a known mediator of wounding stress. These findings imply that expression of the cytosolic Cu/Zn-SOD gene is regulated in a species-specific manner.…”
Section: Northern Blot Analysesmentioning
confidence: 98%
“…The plant SOD gene has been cloned from corn (Cannon, White, & Scandalios, 1987), cassava (Lee, Kim, You, Kwon, & Kwak, 1999), rice (Wang, Wang, & Wang, 2007), evodia (Wu, Gao, Pan, Luo, & Zhang, 2011), camellia oleifera (Guo & Zhang, 2012), and been applied to improve the plant resistance in recent years. For example the tobacco overexpressing cytosolic Cu/Zn SOD was more tolerant to acute doses of ozone than the control (Pitcher & Zilinskas, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…SODs constitute the first line of defense against highly toxic superoxide radicals by converting superoxide to H 2 O 2 and molecular oxygen. SOD activity has been reported to increase in response to stress conditions such as high irradiance, low temperature (Mauro et al, 2005) drought and high temperature (Lee et al, 1999;Rhizhsky et al, 2002;Selote and KhannaChopra, 2006). In our studies also chloroplastic Cu/Zn SOD protein content and activity increased in response to high temperature, high light and in water stress recovered plants (Fig.…”
Section: Discussionmentioning
confidence: 95%